2017
DOI: 10.1080/09638237.2017.1340603
|View full text |Cite
|
Sign up to set email alerts
|

Assessing vocational outcome expectancy in individuals with serious mental illness: a factor-analytic approach

Abstract: The VOES is a brief, reliable and valid instrument for assessing vocational outcome expectancy in individuals with SMI that can be integrated into SDT/SET as a vocational rehabilitation engagement and recovery model in psychiatric rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…By taking several measurements over two days during both events, the authors found that the POMS reflected a more positive mood profile during the simulated event in contrast to the competition. In addition to the context of the situation, the outcome evaluated against outcome expectancy (Iwanaga et al 2017) may influence one's psychological state. In a swimming competition total mood disturbance, and several other indices of negative affect, increased in the 'failure' group, while few negative changes were seen in the 'success' group (Chennaoui et al 2016).…”
mentioning
confidence: 99%
“…By taking several measurements over two days during both events, the authors found that the POMS reflected a more positive mood profile during the simulated event in contrast to the competition. In addition to the context of the situation, the outcome evaluated against outcome expectancy (Iwanaga et al 2017) may influence one's psychological state. In a swimming competition total mood disturbance, and several other indices of negative affect, increased in the 'failure' group, while few negative changes were seen in the 'success' group (Chennaoui et al 2016).…”
mentioning
confidence: 99%
“…Vocational outcome expectations . We used a modified version of the Vocational Outcome Expectancy Scale (VOES; Iwanaga et al, ) to measure vocational outcome expectations. The full VOES was constructed using social cognitive career theory, an extension of Bandura's () self‐efficacy theory, for item development (Lent et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The scale contains 11 items across two factors: the six‐item Positive Vocational Expectancy subscale and the five‐item Negative Vocational Expectancy subscale. Strong psychometric properties were established as evidenced by results from the exploratory factor analysis and confirmatory factor analysis (Iwanaga et al, ). Specifically, results from the exploratory factor analysis and confirmatory factor analysis support the two‐factor scale, with each subscale demonstrating sufficient reliability (α = .79).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome expectancy. VR outcome expectancy was assessed with the Positive Outcome subscale of the Vocational Outcome Expectancy Survey (VOES; Iwanaga et al, 2017). This scale was developed to measure the expected benefits from completing a VR program.…”
Section: Methodsmentioning
confidence: 99%